ETHICAL REFLECTIONS OF PROFESSIONAL NURSE IN CARE THE CHILDREN - Magda Nanuck de Godoy (Universidade Federal do Paraná, 2001)
The objetive of this study is to reflecting about the ethics in care of the child in his entery. This ethics has to be well-founded on the nurse's ability of knowing/doing. On this way, the nurse has refleting about ethics, attitude and humans quality in the care of the child, considering the important report between the ethic care and the necessity of child and his family.